VD_FINDINFO HC / 2012 / 187 vom 9. Februar 2012 - VD Tribunal cantonal (2012)
CALCUL, VALEUR LITIGIEUSE, DÉPENS, RÉSILIATION, BAIL À LOYER, LOYER | 110 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 321 al. 2 CPC (CH), 20 al. 2 TDC, 6 TDC